Is Everything Neutral? - Bernheim, B. Douglas; Bagwell, Kyle (Journal of Political Economy, 1988)
In his well-known analysis of the national debt, Robert Barro introduced the notion of a "dynastic family." This notion has since become a standard research tool, particularly in the areas of public finance and macroeconomics. In this paper, we critique the assumptions upon which the dynastic model is predicated, and argue that this framework is not a suitable abstraction In contexts where the objective is to analyze the effects of public policies. We reach this conclusion by formally considering a world in which each generation consists of a large number of distinct individuals, as opposed to one representative individual. We point out that family linkages form complex networks, in which each individual may belong to many dynastic groupings. The resulting proliferation of linkages between families gives rise to a host of neutrality results, including the irrelevance of all public redistributions, distortionary taxes, and prices. Since these results are not at all descriptive of the real world, we conclude that, in some fundamental sense, the world is not even approximately dynastic. These observations call into question all policy related results based on the dynastic framework, including the Ricardian equivalence hypothesis.